Self-Assembled 3D Actuator Using the Resilience of an Elastomeric Material - Hashimoto, Naoki; Shigemune, Hiroki; Minaminosono, Ayato; Maeda, Shingo; Sawada, Hideyuki (Frontiers in Robotics and AI, 2020)
Self-folding technologies have been studied by many researchers for applications to various engineering fields. Most of the self-folding methods that use the physical properties of materials require complex preparation, and usually take time to complete. In order to solve these problems, we focus on the elasticity of a material, and propose a model for forming a 3D structure using its characteristics. Our proposed model achieves high-speed and high-precision self-folding with a simple structure, by attaching rigid frames to a stretchable elastomer. The self-folded structure is applied to introduce a self-assembled actuator by exploiting a dielectric elastomer actuator (DEA). We develop the self-assembled actuator driven with the voltage application by attaching stretchable electrodes on the both side of the elastomer. We attempt several experiments to investigate the basic characteristics of the actuator. We also propose an application of the self-assembled actuator as a gripper based on the experimental results. The gripper has three joints with the angle of 120°, and successfully grabs objects by switching the voltage.